STUDY REGARDING THE STATUS OF THE PROSTHETIC FIELD TO EDENTULOUS PATIENTS CANDIDATES TO DENTAL IMPLANTS - Forna Norina; Chetruş Viorica; Agop-Forna Doriana; Curcă Răzvan; Chirilă Adriana Măriuca; Toader Bianca; Ahmed Ashma; Boiangiu Andy Ariel; Lazaruc Dana (Romanian Dental Association for Education, 2019)
Aim of study. The aim of study was to evaluate the prosthetic field status for edentulous patients candidates to dental implants as well as the required guided tissues regeneration procedures. Materials and method. The study group included 297 untreated edentulous patients aged between 30-70 years (99- males, 198 - females), with partial edentation, programmed for implant-prosthetic treatment in Clinical Dental Learning Base of Dental Medicine Faculty, U.M.F. "Grigore T. Popa" Iași and two private dental practices. Anamnesis data, clinical examen, paraclinical examens were recorded in clinical papers and Microsoft Excel database. The bone maxillary and mandibular support was assessed by clinical and radiographic examen. The distribution of Misch classes and osteodensity (Ruben-Duval indices) for maxillary and mandibular prosthetic fields were recorded as well as the required bone addition/augmentation procedures. Results. In maxilary extended edentation, in 38% cases the bone support is classified A/B, in 15% cases the bone support is classified B-w, and 53% cases are classified class C. 55% of the maxillary hemiarcades with extended partial edentation require guided bone regeneration techniques. In mandibullary extended edentation, in 60% cases the bone support is classified A/B, in 13% cases the bone support is classified B-w, and 27% cases are classified class C. Conclusions. Severe bone defects requiring guided bone regeneration techniques are found in 40% of the patients with mandibular extended edentation and 55% of the patients with maxillary extended edentations.